2022
DOI: 10.1186/s12939-022-01803-4
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in community shelters: possibilities to improve chronic care among people experiencing homelessness in Hungary

Abstract: Background Digital health has expanded during the COVID-19 pandemic, while the exclusion of vulnerable populations with limited access to these technologies widens the gap to receive proper care. There is very little data available on the feasibility of telemedicine solutions regarding the chronic care of homeless persons. Methods In our study, 75 participants experiencing homelessness were recruited from four social institutions in Budapest, Hunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…In collaboration with the DocRoom Health Research Program at the Hungarian Charity Service of the Order of Malta (Budapest, Hungary), we have been working together on numerous studies on the issue of how vulnerable groups such as people experiencing homelessness could benefit from digital health technologies. The three main aspects of the joint previous research projects were: attitudes and openness of people experiencing homelessness toward telemedicine ( 19 ), access to digital devices and health-related Internet use among people experiencing homelessness ( 20 ), and the evaluation of a telemedicine pilot project in homeless shelters ( 21 ). The number of participants in each study was N = 98, 662, and 75, respectively.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…In collaboration with the DocRoom Health Research Program at the Hungarian Charity Service of the Order of Malta (Budapest, Hungary), we have been working together on numerous studies on the issue of how vulnerable groups such as people experiencing homelessness could benefit from digital health technologies. The three main aspects of the joint previous research projects were: attitudes and openness of people experiencing homelessness toward telemedicine ( 19 ), access to digital devices and health-related Internet use among people experiencing homelessness ( 20 ), and the evaluation of a telemedicine pilot project in homeless shelters ( 21 ). The number of participants in each study was N = 98, 662, and 75, respectively.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…Overall, our previous research showed that digital health services have great promise in community shelters for managing and preventing health issues [ 29 , 30 ], and this study found that digitally engaged individuals might be important for the success of such services.…”
Section: Discussionmentioning
confidence: 66%
“…When asked about usage patterns, several interviewees spontaneously shared their views on how age differences matter in usage prevalence, outlining that older generations might be less involved and less interested in novel technologies. Several studies, including our previous quantitative research, support that age is a key sociodemographic variable that has an impact on use [ 29 , 30 , 46 , 47 ]. Our quantitative data showed that in access to technology, age did not seem to be a key factor; however, it might be considered as a significant factor when self-evaluating competence in digital literacy skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after the pandemic, with the extension of telehealth policies [12], telemedicine remains an integral part of healthcare delivery to overcome geographic barriers to medical care [10,12,13]. Telemedicine, when provided in community spaces, can expand healthcare access for people experiencing social marginalization including homelessness [14][15][16]. Telemedicine, in addition to other electronic health technologies, have been successfully implemented in the HCV care cascade, specifically to gain access to marginalized populations like PWID [17][18][19][20].…”
Section: Introduction 1background and Rationalementioning
confidence: 99%